Changes in the molecular phenotype of nucleus pulposus cells with intervertebral disc aging. - Xinyan Tang; Liufang Jing; Jun Chen (PLoS ONE, 2012)
Intervertebral disc (IVD) disorder and age-related degeneration are believed to contribute to low back pain. Cell-based therapies represent a promising strategy to treat disc degeneration; however, the cellular and molecular characteristics of disc cells during IVD maturation and aging still remain poorly defined. This study investigated novel molecular markers and their age-related changes in the rat IVD. Affymetrix cDNA microarray analysis was conducted to identify a new set of genes characterizing immature nucleus pulposus (NP) cells. Among these markers, select neuronal-related proteins (Basp1, Ncdn and Nrp-1), transcriptional factor (Brachyury T), and cell surface receptors (CD24, CD90, CD155 and CD221) were confirmed by real-time PCR and immunohistochemical (IHC) staining for differential expression between IVD tissue regions and among various ages (1, 12 and 21 months). NP cells generally possessed higher levels of mRNA or protein expression for all aforementioned markers, with the exception of CD90 in anulus fibrosus (AF) cells. In addition, CD protein (CD24 and CD90) and Brachyury (T) expression in immature disc cells were also confirmed via flow cytometry. Similar to IHC staining, results revealed a higher percentage of immature NP cells expressing CD24 and Brachyury, while higher percentage of immature AF cells was stained positively for CD90. Altogether, this study identifies that tissue-specific gene expression and age-related differential expression of the above markers do exist in immature and aged disc cells. These age-related phenotype changes provide a new insight for a molecular profile that may be used to characterize NP cells for developing cell-based regenerative therapy for IVD regeneration.